2016
DOI: 10.1080/23761407.2015.1086714
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Team Teaching Model for a MSW Capstone Course

Abstract: This exploratory study was embedded in a formative process for the purposes of improving content delivery to an evidence-based practice class, and improving students' performance on a comprehensive exam. A learning and teaching model was utilized by faculty from a three-university collaborative graduate social work program to examine the extent to which course texts and assignments explicitly supported the process, application, and evaluation of evidence-based practices. The model was grounded in a collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…▪ Second-year students indicated that they better recognized relevance of bioscience to nursing. 8 Moore RM, Darby KH, Blake ME 2016 Journal of Evidence-Informed Social Work [ 26 ] Social work Capstone course Master of science Exploratory study-Survey ▪ The more a student embraced the course content, the more confident he/she became in preparing for the comprehensive exam. ▪ All involved (faculty and students) discovered a real sense of empowerment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…▪ Second-year students indicated that they better recognized relevance of bioscience to nursing. 8 Moore RM, Darby KH, Blake ME 2016 Journal of Evidence-Informed Social Work [ 26 ] Social work Capstone course Master of science Exploratory study-Survey ▪ The more a student embraced the course content, the more confident he/she became in preparing for the comprehensive exam. ▪ All involved (faculty and students) discovered a real sense of empowerment.…”
Section: Resultsmentioning
confidence: 99%
“…Moore et al [ 26 ] offered an EBP course for master students of social workers for three universities, with a revised curriculum based on the collaboration of faculty members of the universities. The students’ rate of failure in the comprehensive exam in comparison to the last 3 years decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Team-based learning is conducive to the cultivation of students' independent learning, cooperation and mutual coordination. Micro-video production is conducive to the cultivation of students' hands-on ability and innovative spirit, while competition can stimulate students' interest and fight in learning and improve learning efficiency [4,5,[8][9][10][11][12] . The main evaluation is to set up the main situation for the judgment, which makes the students have to meet the needs of the knowledge and ability preparation as the judgers through independent learning before the evaluation on others and learn imperceptibly in the process of evaluation of others [13,14] .…”
Section: Discussionmentioning
confidence: 99%